(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: A transplant represents a decisive event for patients and their caregivers. This article deals with the attitudes patients and their spouses have towards the transplantation. METHODS: In a cross-sectional study, 121 patients and their spouses were surveyed by questionnaire after a heart, lung, liver or kidney transplant. Attitudes were assessed by means of semantic differentials. Based on the results, an ‘Attitudes towards Transplantation’ Scale was developed. Sense of coherence (SOC-13), quality of life (Sf-36), quality of the relationship (RAS), burnout (BM) and the patient’s emotional response to the transplant (TxEQ-D) were additional psychosocial variables measured in order to assess the association between the attitudes and psychosocial characteristics of transplant patients and their spouses. RESULTS: The majority of patients and their spouses reported positive attitudes towards the transplant, including the attitudes towards medication, their perceived self and fate of being a transplant patient or spouse. Patients and spouses, however, had a negative attitude towards the transplantation in terms of stress and anxiety. Patients reported greater emotional stress from the transplant and rated their post-transplant perceived fate more negatively than their spouses. Attitudes towards the transplant were significantly associated with the sense of coherence and the quality of relationship. CONCLUSION: The attitudes of patients and spouses to different aspects of the transplant itself and to being a transplant patient or spouse should be deliberately reconsidered and facilitated in the psychosocial counselling with regard to the comprehensibility, manageability and meaningfulness of the transplant experience as well as to potential conflicts in the partnership.